THE EFFECT OF ZISWAF FUND RECEIPTS, GROSS NPF, AND MURABAHAH INCOME ON CAR WITH FIRM SIZE AS A MODERATION VARIABLE IN ISLAMIC BANKING IN INDONESIA PERIOD 2018.Q1-2023.Q3 - Afifa, Fania Eka Bella; Budianto, Eka Wahyu Hestya (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2024)
This study aims to determine the effect of Ziswaf Fund Revenue, Gross NPF, and Murabahah Income on Capital Adequacy Ratio (CAR) in Islamic banks in Indonesia, with Firm Size as a moderating variable. This study uses multiple regression analysis models to test the relationship between these variables. The results showed that Murabahah Income, Gross NPF, and Ziswaf Fund Revenue have a significant influence on CAR. Specifically, higher Murabahah Income and Ziswaf Fund Receipts are associated with lower CAR, while higher Gross NPF is associated with higher CAR. Furthermore, this study also examined the moderating effect of firm size on the relationship between these variables and CAR. The results show that the relationship between Murabahah Income and CAR is stronger in large firms, while the relationship between NPF Gross and CAR is stronger in small firms. In conclusion, this study contributes to understanding the relationship between Murabahah Income, Gross NPF, Ziswaf Fund Receipt, and CAR in Indonesian Islamic banks, providing insights for policy makers and stakeholders in the banking industry.